Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
The equation of a line perpendicular to \( y = -x + 7 \) through \( (3, 5) \) is \( y = x + 2 \).
To find the equation of a line perpendicular to \( y = -x + 7 \), we first need to determine the gradient (slope) of the given line. The gradient of \( y = -x + 7 \) is -1. For two lines to be perpendicular, the product of their gradients must be -1. Therefore, the gradient of the perpendicular line will be the negative reciprocal of -1, which is 1.
Next, we use the point-slope form of the equation of a line, which is \( y - y_1 = m(x - x_1) \), where \( m \) is the gradient and \( (x_1, y_1) \) is a point on the line. Here, \( m = 1 \) and the point given is \( (3, 5) \).
Substituting these values into the point-slope form, we get:
\[ y - 5 = 1(x - 3) \]
Simplifying this equation:
\[ y - 5 = x - 3 \]
\[ y = x + 2 \]
Thus, the equation of the line perpendicular to \( y = -x + 7 \) and passing through the point \( (3, 5) \) is \( y = x + 2 \). This method ensures that the new line has the correct gradient and passes through the specified point.
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.